Conflitos socioambientais que afetam a soberania alimentar de comunidades do Cerrado do Pantanal – MT - Valles, Eronaldo Assunção (2018)
This research is part of the daily practice of two culturally unique communities: Quilombo Laranjal (black descendant of slaves) and the Traditional Community Zé Alves. They are formed by peasants who develop activities of food production (agriculture and livestock) and vegetable extractive activities, in family and community, in the municipality of Poconé, Mato Grosso state. The displacement of the agricultural frontier has brought significant environmental damages that threaten the food sovereignty of these populations. Changes in land use and occupation have been characterized in a context of environmental injustice, considering that agribusiness activities are highly predatory and cause serious social and environmental damages. The consequences occur in an unequal way, because the social groups less deprived of technical and financial conditions are the most harmed. Socioenvironmental problems are perceived in several aspects in the daily life of these communities, and this research uses Environmental Education to understand environmental changes and their relationships with food production practices. It is a research that had the methodological contribution of the social map, recognizing that there are groups that have been deprecated regarding the historical process of expansion of the use and occupation of the territory of Mato Grosso. In this sense, I sought, through the narratives of the subjects surveyed, to uncover the processes of expropriation of social groups and their territories. I used several routes in the investigative ways, such as observation in the 7 field-works, political-pedagogical discussion in the 2 seminars mapping social groups and their socioenvironmental conflicts, in addition to the interpretations of 10 semi-structured interviews with peasants in the communities Zé Alves and Laranjal. Among the results, I observed that most of the narrated conflicts have a connection with the use and occupation of space, materialized by the struggle for different groups in aspects related to nature, more specifically to ecological systems. That is, the dispute over the land use occurs using the biotic components (fauna and flora) and abiotic (minerals, soil, water and climate) of the local ecosystem. The main activities identified as generating socio-environmental conflicts are: deforestation, abusive use of pesticides, land dispute, water dispute, mining and burnings. I interpret that Environmental Education and Popular Education gain relevant pedagogical contours, as they question the politics of the current development model that has created a scenario of inequality across the globe. Thus, I believe in the educational process that can show the predatory way of appropriation of nature causing a disastrous picture of socioenvironmental injustices, the hard way of day-by-day struggles, the changes in food habits and the formative processes that offer more dignity and hope for another possible world.